2013
DOI: 10.1074/jbc.m113.478552
|View full text |Cite
|
Sign up to set email alerts
|

Low-density Lipoprotein Receptor-related Protein 1 (LRP1)-dependent Cell Signaling Promotes Axonal Regeneration

Abstract: Background: LRP1 activation is neuroprotective in vitro. The role of LRP1 in axonal plasticity and regeneration is unknown. Results: LRP1-dependent cell signaling that includes TrkC activation promotes axonal growth in the CNS. Conclusion: LRP1 agonists promote regeneration after spinal cord injury. Significance: A significant role is established for LRP1 in axonal growth and regeneration after CNS injury, identifying a novel class of therapeutic targets for neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 56 publications
1
56
1
Order By: Relevance
“…Previously, a correlation between decreased Akt phosphorylation and caspase-3 activation was demonstrated in LRP1 knocked-down neurons (Fuentealba et al, 2009). Another recent study demonstrated that treatment of neurons with LRP1 agonists induces TrkC, Akt, and ERK activation and increases neurite outgrowth (Yoon et al, 2013). Our study found that Akt activation decreased in neurons under ischemic conditions and it was further decreased in the presence of the LRP1 antagonist RAP.…”
Section: Discussionmentioning
confidence: 58%
“…Previously, a correlation between decreased Akt phosphorylation and caspase-3 activation was demonstrated in LRP1 knocked-down neurons (Fuentealba et al, 2009). Another recent study demonstrated that treatment of neurons with LRP1 agonists induces TrkC, Akt, and ERK activation and increases neurite outgrowth (Yoon et al, 2013). Our study found that Akt activation decreased in neurons under ischemic conditions and it was further decreased in the presence of the LRP1 antagonist RAP.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, it was reported that complement protein C1q protected both immature and mature primary cortical neurons against fibrillar and oligomeric Aβ-mediated neurotoxicity possibly through a neuroprotective response that involves the upregulation of LRP1B [118]. Further evidence of the neuroprotective role of LRP-1 was recently found: LRP-1-dependent cell signaling via TrkC activation promoted axonal growth in the CNS after injury, suggesting a clear contribution of LRP-1 to neuronal plasticity [119]. Sagare and colleagues [120] further explored LRP-1 as a target and showed that 3-month treatment of an AD mouse model with LRPIV-D3674G, a mutant receptor with higher affinity to Aβ 40 and Aβ 42 in vitro and lower affinity to other LRP-1 ligands, given subcutaneously at 40 μg/kg/day, reduced Aβ 1-40 and Αβ 1-42 levels in the hippocampus, cortex, and cerebrospinal fluid by 60-80 % and enhanced CBF and hippocampal function at 9 months of age.…”
Section: Changes In Amyloid-β Transportersmentioning
confidence: 96%
“…This interaction might be potentiated by ligand binding to LRP1 . Trk receptors also are required for cell signaling downstream of LRP1 and the NMDA-R in neurons and neuron-like cells (Shi et al, 2009;Yoon et al, 2013). Because we do not have evidence for the function of Trk receptors in LRP1 signaling in Schwann cells (Shi et al, 2009), the activity of other receptor tyrosine kinases merits consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Other LRP1 co-receptors in neurons include Trk receptors and p75 NTR (Shi et al, 2009;Yoon et al, 2013;Stiles et al, 2013). Very little is known about the molecular nature of the LRP1 signaling system in other cell types.…”
Section: Nmda-r Is Necessary For Lrp1 Signaling In Schwann Cellsmentioning
confidence: 99%
See 1 more Smart Citation